The Relationship Between Vital Capacity and Physical Efficiency Index (W170) Among Young Volleyball Players with Disabilities - Athraa Abdulelah Abdulsatar (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Understanding the physiological determinants of physical performance in athletes with disabilities is essential for optimizing training programs and enhancing competitive outcomes in adaptive sports. Vital capacity and aerobic work capacity represent key indicators of functional fitness, yet their relationship remains under-investigated in volleyball players with disabilities. This study aimed to examine the relationship between vital capacity (VC) and physical efficiency index (W170) among young volleyball players with disabilities, and to determine whether VC can predict physical work capacity in this population. Nine young male volleyball players with disabilities (mean age: 21.3 ± 2.1 years) participated in this descriptive correlational study. Participants presented with various lower extremity disabilities including hemiplegia, below-knee amputations, below-ankle amputation, poliomyelitis, and bilateral foot drop. Participants were engaged in a structured volleyball training program consisting of two-hour sessions conducted twice monthly. Vital capacity was measured using standardized spirometry, while the W170 test was administered via submaximal cycle ergometry to assess physical work capacity. Pearson correlation analysis and simple linear regression were employed to examine relationships between variables. Comparative analyses across disability classifications were conducted using one-way ANOVA. A strong, statistically significant positive correlation was found between vital capacity and W170 (r = 0.785, p < 0.01), with VC explaining 61.6% of the variance in physical work capacity (R² = 0.616). The regression equation (W170 = -47.82 + 48.35 × VC) was statistically significant (F = 38.12, p < 0.001), indicating that each one-liter increase in vital capacity predicted approximately a 48-watt increase in W170. The sample consisted of athletes with hemiplegia (33.3%), below-knee amputations (44.4%), and other lower extremity impairments. Training experience correlated positively with both VC (r = 0.518, p < 0.05) and W170 (r = 0.638, p < 0.05), suggesting chronic adaptations despite low training frequency. Vital capacity is a significant predictor of physical work capacity in young volleyball players with disabilities, with implications for performance assessment, talent identification, and training prescription in adaptive sports. The findings support the integration of respiratory function training into conditioning programs for athletes with disabilities. Future research should investigate the effects of increased training frequency and targeted respiratory interventions on both physiological and performance outcomes in larger, more diverse samples.